Lithuania after politics? - Navickas, Andrius (Political Preferences, 2017)
The results of the Seimas elections in 2016 year have revealed one of the greatest transformation in Lithuanian party system since its formation in1992 m. Though there are similarities between the political processes in Lithuania, Poland Hungary, the Czech Republic, however it is important to stress important differences, which enable us to speak about the unique “Lithuanian way”. First of all, the new political group, which dominates in Lithuanian political system after the elections – Lithuanian Peasants and Green union (LPGU), not only rejected the tradition political continuum of “right-left”, but also has not fit to the main political cleavage in postcommunist political system of Lithuania between ex-communist and anti-communist. Second, the elections revealed the huge crisis of democracy based on political parties in Lithuania. The dissatisfaction with parties, as the main actors in modern liberal democracy, constantly increases. Third, we can speak about the decisive victory of anti-politics in Lithuania, the marginalization of the political deliberations and the political competence in the governance of the state. This triumph of anti-politics in Lithuania is not the outcome of the cultural tradition of anti-politics which was strong in Poland and Czechoslovakia (but not in Lithuania) during the 20th century [Havelka, 2016], but rather the price which we have to pay for the invasion of the mentality of consumption in political sphere. The main task of this article – to foster the discussion about the future of liberal democracy in Lithuania, about the prospects of political parties and the threat of the final victory of “consumer” against “citizen”, also about the lessons of political life in Lithuania for other post-communist states. Key words: elections, anti-politics, consumer, citizen, parties